Sharing Session Tata Tulis Karya Ilmiah: Meningkatkan Ide dan Kreativitas Dalam Menyusun Karya Tulis Ilmiah - Nugroho, Handi Wilujeng; Hamidi, Kurniawan; Nasution, Rivarra Syara; Kurniadi, Deri; Saputri, Anggraini Dwi (Journal of Social and Community Service, 2023)
This activity aims to increase students' insight into the importance of writing scientific papers, good scientific writing techniques, and how to use appropriate references. This event will be held online via the Zoom application on July 29 2023 with the theme "Increasing Ideas and Creativity in Compiling Scientific Work." The activity was attended by 44 participants from various scientific disciplines and institutions. The resource person provided insight into strategies for finding ideas, research gaps, and using the Mendeley application for reference management. Based on the questionnaire, more than 90% of participants expressed interest in taking further training on writing scientific papers. The result of this activity is an increase in participants' understanding of the scientific writing process as well as the establishment of collaboration between universities for future research.